Experimental research on the cooling effect of a novel two-phase closed thermosyphon with semiconductor refrigeration in permafrost regions - Yongheng Liu; Ji Chen; Chuanglu Wang; Youqian Liu; Shouhong Zhang; Tianchun Dong; Yaojun Zhao; Juncheng Wang; Xi Wang; Xin Hou (Case Studies in Thermal Engineering, 2024)
Hybrid two-phase closed thermosyphon (TPCT) artificial ground freezing technique is an effective cooling strategy adaptable to different geological and meteorological conditions in permafrost regions. Previous studies have focused on the feasibility of hybrid TPCT with little attention given to the cooling characteristics and long-term effects of this technique under actual environmental conditions. In this study, a novel structured semiconductor refrigeration device, with simple structure, small size, and wide operating temperature range, was designed and manufactured to act as the active condenser of a hybrid TPCT, and the cooling effect of this device was investigated during a two-year field test under stable power supply. This study showed that: 1) The minimum (maximum) average temperature of the semiconductor refrigeration two-phase closed thermosyphon (SRTPCT) evaporator was 0.5 (2.1) °C lower than the TPCT evaporator. The average ground temperature decreased by 0.3 °C, and the permafrost table rose to 0.2 m at 1 m from the evaporators around SRTPCT. The semiconductor refrigeration device added more than 9.75 MJ of cold storage to the soil around the TPCT evaporator during an operating cycle. 2) The optimal working period for the semiconductor refrigeration device was from June to October, and the cooling effect was better when the ambient temperature was low in the warm season. 3) As active condenser of hybrid TPCT in permafrost regions, semiconductor refrigeration device has a larger heat transfer power enhancement for TPCTs than vapor compression refrigeration device in the warm season, and vice versa in the cold season, as well as a higher heat transfer power enhancement for TPCTs than adsorption refrigeration device. The results of this study provide relevant parameters and references for the design and engineering application of future SRTPCT.